Lessons learnt from TB screening in closed immigration centres in Italy - Crepet, Anna; Repetto, Ernestina; Al Rousan, Ahmad; Sané Schepisi, Monica; Girardi, Enrico; Prestileo, Tullio; Codecasa, Luigi; Garelli, Silvia; Corrao, Salvatore; Ippolito, Giuseppe; Decroo, Tom; Maccagno, Barbara (International health, 2016)
Background Between June 2012 and December 2013 Médecins Sans Frontières launched a pilot project with the aim of testing a strategy for improving timely diagnosis of active pulmonary TB among migrants hosted in four centres of identification and expulsion (CIE) in Italy. Methods This is a descriptive study. For active TB case finding we used an active symptom screening approach among migrants at admission in four CIE's. Here we describe the feasibility and the yield of this programme. Results Overall, 3588 migrants were screened, among whom 87 (2.4%) had a positive questionnaire. Out of 30 migrants referred for further investigations, three were diagnosed as having TB, or 0.1% out of 3588 individuals that underwent screening. Twenty-five (29%, 25/87) migrants with positive questionnaires were not referred for further investigation, following the doctors' decision; however, for 32 (37%, 32/87) migrants the diagnostic work-out was not completed. In multivariate analyses, being over 35 years (OR 1.7; 95% CI 1.1–2.6) and being transgender (OR 4.9; 95% CI 2.1–11.7), was associated with a positive questionnaire. Conclusions TB screening with symptom screening questionnaires of migrants at admission in closed centres is feasible. However, to improve the yield, follow-up of patients with symptoms or signs suggestive for TB needs to be improved.